Quality of life and psychological consequences in elderly patients after a hip fracture: a review - Alexiou KI (Dove Medical Press, 2018)
Konstantinos I Alexiou,1 Andreas Roushias,2 Sokratis E Varitimidis,1 Konstantinos N Malizos1 1Department of Orthopaedic Surgery and Musculoskeletal Trauma, Medical School, University of Thessaly, Larissa, Greece; 2Orthopaedic Department, Apollonion Private Hospital, Nicosia, Cyprus Abstract: Fractures due to fragility of the bone around the hip joint have become a major public health issue, presenting with an increasing incidence due to the growth of the elderly population. The purpose of this review was to evaluate the impact of hip fractures on the quality of life (QoL), health status (HS), functioning, and psychological parameters, and factors influencing the outcome and the appropriate interventions for improvement of elderly patients. A systematic electronic search of the relevant literature was carried out using the CINAHL, Cochrane, EMBASE, Medline (OvidSP), and PubMed databases spanning the time period from their establishment up to January 2017. Forty-nine randomized controlled trials or prospective cohort studies reporting the QoL and psychological outcomes were assessed by using standardized questionnaires. Patients with a hip fracture who were older than 65 years, were included in the analysis. In the majority of elderly patients, the hip fracture seriously affected physical and mental functioning and exerted a severe impact on their HS and health-related QoL (HRQoL). Moreover, most of the patients did not return to prefracture levels of performance regarding both the parameters. The levels of mental, physical, and nutritional status, prior to the fracture, comorbidity, and female gender, in addition to the postoperative pain, complications, and the length of hospital stay, were the factors associated with the outcome. Psychosocial factors and symptoms of depression could increase pain severity and emotional distress. For the displaced femoral neck fractures, the treatment with total hip arthroplasty or hemiarthroplasty, when compared to the treatment with internal fixation, provided a better functional outcome. Supportive rehabilitation programs, complemented by psychotherapy and nutritional supplementation prior to and after surgery, provided beneficial effects on the HS and the psychosocial dimension of the more debilitated patients’ lives. Lack of consensus concerning the most appropriate HRQoL questionnaires to screen and identify those patients with more difficulties in the psychosocial functions, demonstrates the necessity for further research to assess the newer outcome measurement tools, which might improve our understanding for better care of patients with hip fractures. Keywords: hip fractures, quality of life, psychological outcomes, elderly, health status